Evaluation of human papillomavirus testing for squamous cell carcinoma of the tonsil in clinical practice. Issue 4 (23rd February 2011) - Thavaraj, Selvam; Stokes, Angela; Guerra, Eliete; Bible, Jon; Halligan, Eugene; Long, Anna; Okpokam, Atuora; Sloan, Philip; Odell, Edward; Robinson, Max
Abstract : Background: Oncogenic human papillomavirus (HPV)-associated oropharyngeal squamous cell carcinoma (SCC) is a subtype of head-and-neck cancer with a distinct clinical and prognostic profile. While there are calls to undertake HPV testing for oropharyngeal SCCs within the diagnostic setting and for clinical trials, there are currently no internationally accepted standards. Methods: 142 tonsil SCCs were tested using p16 immunohistochemistry (IHC), high-risk HPV DNA in situ hybridisation (ISH) and HPV DNA polymerase chain reaction (PCR; GP5+/6+ primers). Results: There were high levels of agreement between pathologists for p16 IHC and HPV ISH scoring; however, around 10% of HPV ISH cases showed some interobserver discrepancy that was resolved by slide review. The combination of p16 IHC and HPV ISH classified 53% of the samples as HPV-positive, whereas the combination of p16 IHC and HPV PCR classified 61% of the samples as HPV-positive. By employing a three-tiered, staged algorithm (p16 IHC/HPV ISH/HPV PCR), the authors were able to classify 98% of the cases as either HPV-positive (p16 IHC+/HPV DNA+; 62%) or HPV-negative (p16 IHC−/HPV DNA−; 35%). Conclusions: The current study suggests that using a combination of p16 IHC/HPV ISH/HPV PCR, in a three-tiered, staged algorithm, in conjunction with consensus reporting of HPV ISH, leads to less equivocal molecular classification. In order to ensure consistent reporting of this emerging disease, it is increasingly important for the head-and-neck oncology community to define the minimum requirements for assigning a diagnosis of 'HPV-related' oropharyngeal SCC in order to inform prognosis and for stratification in clinical trials.